Dental mesowear patterns challenge the hypothesis of a 1.7 Ma transition to open grasslands in South Africa's Cradle of Humankind - Megan Malherbe; Martin Haeusler; Robyn Pickering; Deano Stynder (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

Challenging the antiquity of the Cradle of Humankind, South Africa: Geochronological evidence restricts the age of Eurotomys bolti and Parapapio to less than 2.3 Ma at Waypoint 160, Bolt's Farm - Tara R. Edwards; Robyn Pickering; Tom L. Mallett; Andy I.R. Herries (Journal of Human Evolution, 2023)

Ecometrics and the paleoecological implications of Pleistocene faunas from the western coastal plains of the Cape Floristic Region, South Africa - J. Tyler Faith; David R. Braun; Benjamin Davies; Larisa R. G. DeSantis; Matthew J. Douglass; Irene Esteban; Vincent Hare; Naomi E. Levin; Julie Luyt; Robyn Pickering; Mitchell J. Power; Judith Sealy; et al. (Journal of Quaternary Science, 2020)
The Pleistocene ungulate communities from the western coastal plains of South Africa's Cape Floristic Region (CFR) are diverse and dominated by grazers, in contrast to the region's Holocene and historical faunas, which are relatively species‐poor and dominated by small‐bodied browsers and mixed feeders. An expansion of grassy habitats is clearly implied by the Pleistocene faunas, but the presence of ruminant grazers that cannot survive the summer dry season typical of the region today suggests other important paleoecological changes. Here we use dental ecometrics to explore the paleoecological implications of the region's Pleistocene faunas. We show that the dental traits (hypsodonty and occlusal topography) of the ungulates that occurred historically in the CFR track annual and summer aridity, and we use these relationships to reconstruct past aridity. Our results indicate that the Pleistocene faunas signal paleoenvironments that were on average less arid than today, including during the summer, consistent with other lines of evidence that suggest a higher water table and expansion of well‐watered habitats. Greater water availability can be explained by lower temperature and reduced evapotranspiration during cooler phases of the Pleistocene, probably coupled with enhanced groundwater recharge due to increased winter precipitation.

Re‐analysis of key evidence in the case for a hemispherically synchronous response to the Younger Dryas climatic event - Helen Green; Jon Woodhead; John Hellstrom; Robyn Pickering; Russell Drysdale (Journal of Quaternary Science, 2013)

Re‐analysis of key evidence in the case for a hemispherically synchronous response to the Younger Dryas climatic event - Helen Green; Jon Woodhead; John Hellstrom; Robyn Pickering; Russell Drysdale (Journal of Quaternary Science, 2013)
A south‐east Australian speleothem stable isotope record displaying an apparent cooling synchronous with the northern hemisphere Younger Dryas climate event (12.9–11.7 ka) has significantly influenced scientific thinking on the climatic response of the southern hemisphere following the Last Glacial Maximum. This is one of very few records displaying such a response, and yet the cooling was inferred from substantial extrapolation between just three uranium‐series ages. Technological advances since then have produced major improvements in both the spatial resolution and the accuracy of uranium‐series geochronologies. Re‐analysis of this sample has yielded ages of 7.96 ± 0.36 to 7.69 ± 0.33 ka for the interval previously inferred to span the Younger Dryas, and reveals a substantial hiatus in deposition from 6.93 ± 0.64 to 1.83 ± 0.16 ka. These data not only refute the original evidence for an inter‐hemispheric synchroneity of the Younger Dryas but also reject any evidence for neoglacial conditions at 3 ka. Copyright © 2013 John Wiley & Sons, Ltd.

Ecological and Toxicological Effects of Exposure to an Acidic, Radioactive Tailings Storage - John Read; Robyn Pickering (Environmental Monitoring and Assessment, 1999)